Authentication method in SWIM based on improved Diameter/EAP-MD5 - Zhi-jun WU; Ting ZHAO; Jin LEI (Tongxin xuebao)
System wide information management (SWIM) provides the civil aviation information exchange and data sharing function by using service-oriented architecture (SOA). Based on the analysis of SWIM architecture and the sub-protocol EAP-MD5 of Diameter, the security vulnerable of authenticating process in standard Diameter/EAP-MD5 is explored, the EAP-MD5 authentication protocol is improved, and the SWIM authentication service based on Diameter is studied, then the SWIM authentication method based on improved Diameter/EAP-MD5 protocol is proposed. Experi-ments on the security of SWIM authentication service based on Diameter are performed in SWIM simulation environ-ment, results show that the improved Diameter/EAP-MD5 authentication method can enhance the security of SWIM au-thentication and guarantee SWIM security service.